Governo eletrônico e transparência: a publicização das contas públicas das capitais brasileiras - Prado, Otavio (2004)
The main purpose of this work is to analyze the influence of the electronic government for democracy. This issue allows different approaches and this work focuses on the evaluation of administrative transparency and availability of public information in governmental websites. The empirical analysis evaluated the public rendering of accounts of all the Brazilian state capitals, in fulfillment to the federal laws of Contas Públicas (Appropriations Act) and Responsabilidade Fiscal (Fiscal Responsibility Act). For this, a method of evaluation of governmental websites was created, allowing the analysis of the main indicators concerning administrative transparency. The results of this research suggested the main components for transparency, which allow us to relate them to what it is reported in the literature on the subject. As a final result, it is intended to contribute for the understanding of one of the basic components of the representative democracy: the transparency of the public acts, collaborating to increase the knowledge on the possible impacts of the electronic government in the modern society.